CeO2 Nanoparticles Seed Priming Increases Salicylic Acid Level and ROS Scavenging Ability to Improve Rapeseed Salt Tolerance - Mohammad Nauman Khan; Yanhui Li; Chengcheng Fu; Jin Hu; Linlin Chen; Jiasen Yan; Zaid Khan; Honghong Wu; Zhaohu Li (Global Challenges, 2022)
Abstract Soil salinity is a major issue limiting efficient crop production. Seed priming with nanomaterials (nanopriming) is a cost‐effective technology to improve seed germination under salinity; however, the underlying mechanisms still need to be explored. Here, polyacrylic acid coated nanoceria (cerium oxide nanoparticles) (PNC, 9.2 nm, −38.7 mV) are synthesized and characterized. The results show that under salinity, PNC priming significantly increases rapeseed shoot length (41.5%), root length (93%), and seedling dry weight (78%) compared to the no‐nanoparticle (NNP) priming group. Confocal imaging results show that compared with NNP group, PNC priming significantly reduces reactive oxygen species (ROS) level in leaf (94.3% of H2O2, 56.4% of •O2−) and root (38.4% of H2O2, 41.3% of •O2−) of salt stressed rapeseed seedlings. Further, the results show that compared with the NNP group, PNC priming not only increases salicylic acid (SA) content in shoot (51.3%) and root (78.4%), but also upregulates the expression of SA biosynthesis related genes in salt stressed rapeseed. Overall, PNC nanopriming improved rapeseed salt tolerance is associated with both the increase of ROS scavenging ability and the increase of salicylic acid. The results add more information to understand the complexity of mechanisms behind nanoceria priming improved plant salt tolerance.